Utvärdering av CTI på virkesfordon - Åkerlund, Martin (2007)
The low bearing capacity of roads during the spring thaw and periods in the autumn leads every year to increases costs for Holmen Skog. To reduce costs and increase accessibility Holmen Skog decided to install and test a CTI-system. Central tire inflation (CTI) is a system that makes it possible to monitor and vary a vehicle's tire inflation pressures from the cabin, while the vehicle is in motion. When tire pressures are reduced, the area of the contact surface between the tire and the road increases, thus reducing the ground pressure.